Fouling studies on hydrophobic PVDF-bentonite hollow fiber membrane during membrane distillation of palm oil mill effluent - N. A. S., Muhamad; N. M., Mokhtar; W. J., Lau; A. F., Ismail; R., Naim (Elsevier, 2022)
Membrane distillation (MD) is one of the emerging methods that can be adopted for oily wastewater treatment. However, the problems associated with membrane surface fouling may impede its separation efficiency. In this work, we performed a fouling study using self-synthesized polyvinylidene difluoride (PVDF)-bentonite hollow fiber membrane (HFM) to treat palm oil mill effluent (POME) via direct contact membrane distillation (DCMD). To date, there is no report on POME treatment using MD technology based on PVDF-bentonite HFM. The fouling tendency was identified based on the membrane's permeate flux and pollutant rejection. The fouled membranes after POME treatment were characterized based on its morphology, functional group, water contact angle, surface roughness and mechanical strength. The results showed that the average permeate flux of MD was 3.34 kg/m2·h over 72-h operation. The membrane showed good performance in separating pollutants with >95 % removal rate recorded for chemical oxygen demand, nitrate nitrogen, total suspended solid, total dissolved solid, color and turbidity. However, based on the post-characterization analysis, the used membranes still suffered from fouling after 72-h DCMD test. Thus, an in-depth investigation into the prevention and control of membrane fouling is still necessary for the POME treatment using DCMD.